Synthesis and characterization of 4-layered functionally graded Al-Al2O3 MMC - Jakie Sheraf; Darius Gnanaraj S (Heliyon)
Functionally graded materials (FGMs) have a gradient of properties along their dimensions. These materials are resistant to delamination, making them ideal for replacing conventional composites in various fields of engineering. Among FGMs, aluminium-based FGMs are receiving a lot of attention due to their versatility. Al-Al2O3 FGMs, in particular, are widely preferred in the aerospace and automobile sectors. This study involves synthesizing a 4-layered FG Al-Al2O3 MMC through PM. The material is subjected to impact, compression, and hardness tests, to assess its mechanical properties. To understand the characteristics of the material, Optical microscopy, SEM, and XRD are carried out. The powder metallurgy route produces FG MMCs with improved properties. The material exhibited an impressive hardness of 183 HV at the top layer, which is higher than similar FGMs and FGMs fabricated via Centrifugal Casting. The compressive strength of Al-Al2O3 FGM is 138 MPa and the impact strength is 16.25 kJ/m2. Owing to the improved properties and FGMs being resistant to delamination mode of failure the study recommends the material as a replacement for conventional Al-Al2O3.